An Analysis of Arabic Language Curriculum Development in Indonesia - Rufaiqoh, Elok; Sutiah, Sutiah; Ulum, Samsul; Yaqin, Muhammad ‘Ainul; Nuruddin, Ahmad; Aloraini, Mohammed Ahmed Mohammmed (UIN ANTASARI, 2024)
Curriculum development must be considered according to the times, the development of science, the needs of students, and the needs of society. In Indonesia, curriculum development from the Learning Design Curriculum (1947) is currently being implemented. The purpose of this paper is to understand the approaches used in curriculum development, and to analyze the development of the Arabic language curriculum in Indonesia. The results of this study indicate that the approaches used in curriculum development are both the administrative and grassroots approach, while the development of the Arabic language curriculum in Indonesia begins with the 1964 curriculum, spanning all the way to the 2022 independent curriculum. Curriculum changes over time have been carried out in a balanced and proportional manner. This is reflected in the teaching of Arabic language skills, which are taught to continue to experience development and refinement. In addition, the orientation of learning Arabic is not only for studying religion, but also oriented toward the realization of Arabic language competence, communicative competence, and cultural competence.